Labour market effects of trade in a small open economy - Agnes Kügler; Klaus S. Friesenbichler; Cornelius Hirsch (Austrian Institute of Economic Research (WIFO), 2021)
Austria is a small open economy that in the last decades underwent two different waves of increasing trade integration: one with Eastern Europe and one with China. This paper studies the effects of increases in trade with China and Eastern Europe on labour market dynamics in Austrian NUTS-4 regions for two ten-year periods between 1995 and 2015. Given the limited data available, the current analysis could not identify significant effects on aggregate labour dynamics neither for rising imports from Eastern Europe or China, nor for rising exports to Eastern Europe. However, there is weak evidence that exports to China have facilitated employment growth, especially in high quality segments. Overall, these results add a cautious perspective to the discussion of import competition.
Keywords: F16; J13; R11; 330; Trade; Employment; China; Eastern Europe; Austria